Evaluation of horticultural traits and seed germination of Tacca chantrieri 'André - -, Krisantini; Wiendi, Ni Made Armini; Palupi, Endah Retno (Agriculture and Natural Resources, 2017)
Tacca chantrieri André is a perennial plant belonging to the Taccaceae family. T. chantrieri is known as the‘bat flower’ or ‘bat plant’ due to its unique black bracts that resemble bats. It has the potential to be commercialized as an indoor, flowering, ornamental plant due to its unique flower morphology and shade tolerance. The distribution of T. chantrieri in its natural habitat has contracted due to land clearing and habitat destruction to the extent that it is now very hard to find in its traditional natural environment. The objectives of this study were to evaluate the morphological characteristics of T. chantrieri, to evaluate seed germination in vivo and in vitro, and in vitro culture of the plant using standard Murashige and Skoog (MS) media. Only 10% of the seeds germinated in 22 wk. An evaluation of the non-germinated seed showed that 42% of the seeds did not have embryos. In vitro culture using the standard MS media resulted in 3-7 new shoots growing from the basal parts of the seedlings after 22 wk, and each shoot further developed 4-7 shoots following transfer to MS media supplemented with indole acetic acid (IAA) at 0.25-0.75 mg/L and N6-benzyladenine (BA) at 1-2 mg/L. These results indicate that even though propagation protocols should be further developed, in vitro propagation using standard MS media supplemented with combinations of IAA and BA provides a more effective way to propagate T. chantrieri when compared to the conventional propagation techniques. This information will be useful for introducing T. chantrieri to the new ornamental plant market and to conservation efforts for this species.